A sudden light - Stein, Garth (Simon & Schuster, 2014)
"In the summer of 1990, 14-year-old Trevor Riddell gets his first glimpse of Riddell House. Built from the spoils of a massive timber fortune, the legendary family mansion is constructed of giant, whole trees, and is set on a huge estate overlooking Puget Sound. Trevor's bankrupt parents have begun a trial separation, and his father, Jones Riddell, has brought Trevor to Riddell House for the summer with a goal: he will join forces with his sister, Serena, to dispatch Grandpa Samuel--who is flickering in and out of dementia--to a graduated living facility, sell off the house and property for development into "tract housing for millionaires," divide up the profits, and live happily ever after. But Trevor soon discovers there's someone else living in Riddell House: a ghost with an agenda of his own. For while the land holds tremendous value, it is also burdened by the final wishes of the family patriarch, Elijah, that it be allowed to return to untamed forestland as a penance for the millions of trees harvested over the decades by Riddell Timber. As he uncovers secrets of his family's past that are hidden deep within the house, guided by the whisperings of the ghost, Trevor discovers a legacy of family trauma and terrible guilt. The ghost will not rest until Elijah's wish is fulfilled, and Trevor's willingness to face the past holds the key to his family's future"--